Somatic pathology in patients witj psoriasis - L. A. Yusupova; A. F. Latypova; R. G. Tukhbatullina (Лечащий Врач, 2021)
The article estimates the frequency of detection of concomitant somatic pathology in patients with psoriasis. The study included 107 psoriasis patients aged 19 to 75 years and older. Anamnesis of the disease was analyzed, which contains information about the causes of the disease and its duration, previous treatment, and trigger factors. The clinical method of the study included a General clinical examination of the patient, including consultations with related specialists to conclude the presence of concomitant somatic pathology or clarify the severity of an existing disease and recommendations for treatment and dynamic follow-up. The study was carried out clinical evaluation of the skin and mucous membranes, assessment of localization skin process, nature of the disease, definition of limitations, seasonality, duration of psoriasis, the effect of earlier therapy, time of recurrence. According to the results of the study, 83.1% of the examined patients have somatic pathology, which is dominated by pathology of the cardiovascular system, digestive organs, respiratory system and ENT organs. The features of the distribution of comorbidities in patients with psoriasis, which should be taken into account when drawing up a treatment plan for such patients, were revealed.